Microencapsulação de óleo essencial de orégano (Origanum vulgare L.) e aplicação em filmes extrusados de amido de mandioca e poli (adipato co-tereftalato de butileno) - Paulo, Ana Flávia Sampaio (2020)
Packages based of biodegradable polymers have been produced in substitution of synthetic packages and may have in its composition antioxidants and antimicrobials, aiming to obtaining active packaging. Among the substances that can be used in its production, the oregano essential oil stands out for its broad spectrum of antimicrobial and antioxidant action. However, due their volatility it can be easily degrade during film production by extrusion due to direct exposure to heat, pressure and oxygen. In this sense, microencapsulation can protect and preventing its degradation. The objective of this work was to develop and characterize biodegradable films from blends of cassava starch and poly (butylene adipate coterephthalate) (PBAT) by blow extrusion with the incorporation of oregano essential oil microparticles obtained by spray drying. The microparticles were produced and characterized in terms of encapsulation efficiency, morphology, mean diameter, and size distribution. The films were elaborated by blown extrusion and were characterized concerning to color and opacity, mechanical properties, water solubility, water vapor permeability (WVP), antioxidant capacity, morphology, thermogravimetric analysis and antimicrobial activity. The microparticles showed 65.7% of encapsulation efficiency, irregular spherical shape, and a mean diameter of 9.45 μm. The films containing oregano essential oil microparticles (FM) showed lower values for tensile strength (2.8 MPa), Young's modulus (14.43 MPa), and elongation (433.5%). The degradation temperatures suggest that incorporating OEO into films in encapsulated form may contribute to thermal stability. The free and encapsulated OEO not affected WVP and water solubility of the films (2.04-2.05 x 10-7 g h-1 m-1 Pa1 e 6.25-9.65%, respectively, p > 0.05). Although FM and FO (film with free oil) films showed a significant concentration of total phenolic compounds and antioxidant capacity, the amount of OEO present in the films was not sufficient to show antimicrobial activity. Therefore, the results obtained in this work suggest that the incorporation of free and microencapsulated oil allowed the obtaining films with antioxidant properties.